Pengaruh Capital Adequacy Ratio (Car), Net Interest Margin (Nim), Loan To Deposit Ratio (Ldr) dan Non Performing Loan (Npl) Terhadap Return On Assets (Roa) Pada Pt. Bank Mandiri (Persero). Tbk - Hidayati Hidayati; Yuvia Yuvia (Fakultas Ekonomi Universitas Bangka Belitung, 2015)
This study analyzed the effect of solvency ratios, profitability ratios, liquidity ratios and earning assets ratios to Return On Assets (ROA) at PT Bank Mandiri (Persero), Tbk. Return On Assets (ROA) is used because it is able to count the ability of bank management to obtain profit on the whole. It is important because bank is a form of financial company which relies on public trust. The bank risk is much greater than the non bank companies. This technique in this study used purposive sampling which is the sampling get in certain consideration. The data used in this study were obtained from the Financial Highlights of PT Bank Mandiri (Persero), Tbk from 2000 to 2011. The analysis technique that used is multiple linear regression using SPSS version 20. The hypothesis testing using the F test and t test and also using classical assumption test involve multikolonierity test, autocorrelation test, heteroscedasticity test and normality test. Based on the study, it can be concluded that the Capital Adequacy Ratio variable has positive effect although insignificant on Return On Assets, Net Interest Margin variable has negative effect although insignificant on Return On Assets, Loan to Deposit Ratio variable has positive and significant effect on Return On Assets and Non-performing Assets variable has negative and significant effect on Return on Assets. This study obtained a value of Adjusted R2 = 0.911, it means that 91.1% Return On Assets can be explained by the independent variables, namely the Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) and the remain 8.9% is explained by other factors in the outside of regression model.